EDUCATION OF FILL MY PLATE COMIC ON OVERWEIGHT ELEMENTARY SCHOOL STUDENTS - Joyeti Darni; Retno Wahyuningsih; Lalu Juntra Utama; Suhaema Suhaema; Abdul Salam (Poltekkes Kemenkes Mataram, 2022)
Background: In the lifestyle shift in Indonesian society, consumption patterns are high in calories, high in simple sugars, and low in fiber and not balanced with sufficient physical activity. Nutrition education can prevent the increasing prevalence of obesity and overweight. An approach to the client is needed in solving problems to change the pattern of life to be healthier and better. Students in Elementary schools tend to prefer illustration books in realistic or cartoon form. Comics have an excellent visual media function in helping to increase knowledge of balanced nutrition, and it is hoped that this will influence the behavior of balanced nutrition. The purpose is to determine the effect of providing comic education Fill My Plate on the energy of elementary school children with excess nutritional status. Methods: This quasi-experimental study involved 60 students who were divided into treatment groups by providing education on comics Fill My Plate and a control group giving education without comics Fill My Plate energy data analysis in both groups using paired t-test. Research Result: The results showed an influence between the energy before and after giving education on comics Fill My Plate in the treatment group (P = 0.000), while the control group had no effect (p = 0.897). Conclusion: Providing education using comics Fill My Plate affected reducing energy in elementary school students who have more nutritional status.